Effectiveness of mud-therapy in rheumatic and dermatologic diseases: a systematic review. (30th September 2020) - Mingrone, V M; Paduano, S; Venturelli, F; Marchesi, I; Valeriani, F; Bassi, M C; Borella, P; Bargellini, A
Abstract: Background: Thermal mud therapy alone or in combination with thermal water baths is widely used in clinical practice for the management of rheumatic and dermatologic diseases in many countries. Despite its long history and tradition, its biological action and its clinical effectiveness are still not clear. The aim of this systematic review is to synthetize the current evidence on the mud therapy effects on pain, function and quality of life in patients with rheumatic and dermatologic diseases. Methods: PubMed/Medline, Embase, and Cochrane Library were searched for articles about the comparative effectiveness of mud therapy alone or combined with other therapies on pain, function and quality of life in adults with rheumatic or dermatological diseases without any restrictions of severity. Studies were searched up to 15 October 2019. We included randomized and non-randomized trials and comparative cohort studies, as well as non-comparative case series and case reports only for safety outcomes. The following outcomes were considered: pain assessed by validated scales or through painkillers drugs consumption, function (i.e. muscle tone, joint motility and stiffness) assessed by validated scores, quality of life and autonomy assessed by validated scales and adverse events. Laboratory inflammation parameters were investigated as secondary outcomes. Results: A total of 2, 455 articles were retrieved through database search, remaining 1, 914 records after duplicates removed. The selection by title and abstract led to include 140 studies for full-text evaluation. The screening of full-text is still being carried out. The majority of 140 records assess the effects of mud therapy in patients with osteoarthritis (51 articles), osteoarthrosis (12) and psoriasis (10). Conclusions: Our results will provide a synthesis of the current evidence on the mud therapy effectiveness, useful to evaluate its inclusion within clinical protocols for the treatment of rheumatic and dermatologic diseases. Key messages: The majority of studies report the treatment with mud for rheumatic diseases. The synthesis of the evidence is useful to evaluate the mud therapy as treatment for rheumatic and dermatologic diseases.